5b=5(2,-3)=(10,-15)
a=5b implies:
2m-3n=10
4n-m=-15
Multiplying the second equation by 2:
2m-3n=10
8n-2m=-30
Solving by elimination method:
5n=-20,n=-4
By substituting back n=-4 in equation 1:
2m-3(-4)=10
2m=10-12
2m=-2
m=-1
Therefore, (m,n)=(-1,-4)
Frequently asked questions (FAQs)
What is the measure of the third angle in a triangle if the first two angles measure 40° and 70°?
+
\( \int e^{2x} \, dx \)
+
Math question: What is the measure of the central angle of a circle if the intercepted arc is 120 degrees?